Degenerative Cervical Myelopathy: A Spectrum of Related Disorders Affecting the Aging Spine. (October 2015) - Tetreault, Lindsay; Goldstein, Christina L.; Arnold, Paul; Harrop, James; Hilibrand, Alan; Nouri, Aria; Fehlings, Michael G.
Abstract : Cervical spinal cord dysfunction can result from either traumatic or nontraumatic causes, including tumors, infections, and degenerative changes. In this article, we review the range of degenerative spinal disorders resulting in progressive cervical spinal cord compression and propose the adoption of a new term, degenerative cervical myelopathy (DCM). DCM comprises both osteoarthritic changes to the spine, including spondylosis, disk herniation, and facet arthropathy (collectively referred to as cervical spondylotic myelopathy), and ligamentous aberrations such as ossification of the posterior longitudinal ligament and hypertrophy of the ligamentum flavum. This review summarizes current knowledge of the pathophysiology of DCM and describes the cascade of events that occur after compression of the spinal cord, including ischemia, destruction of the blood–spinal cord barrier, demyelination, and neuronal apoptosis. Important features of the diagnosis of DCM are discussed in detail, and relevant clinical and imaging findings are highlighted. Furthermore, this review outlines valuable assessment tools for evaluating functional status and quality of life in these patients and summarizes the advantages and disadvantages of each. Other topics of this review include epidemiology, the prevalence of degenerative changes in the asymptomatic population, the natural history and rates of progression, risk factors of diagnosis (clinical, imaging and genetic), and management strategies. ABBREVIATIONS: CSM, cervical spondylotic myelopathy DCM, degenerative cervical myelopathy JOA, Japanese Orthopaedic Association mJOA, modified Japanese Orthopaedic Association OPLL, ossification of the posterior longitudinal ligament SCI, spinal cord injury